Specialized Training for Engineers using VR as part of Education 5.0 - Salach, Mateusz; Paszkiewicz, Andrzej; Stęchły, Arkadiusz; Bolanowski, Marek; Strzałka, Dominik (Proceedings of the ACM International Conference on Interactive Media Experiences Workshops (IMXw); 2025: Proceedings of the ACM International Conference on Interactive Media Experiences WorkshopsDO - 10.5753/imxw.2025.9846, 2025)
Preparing society to function in a rapidly changing technological world requires changes to traditional teaching methods. These changes must also be implemented in the education of engineers across various specializations. This study focuses on the potential use of Virtual Reality (VR) environments to enhance the competencies of engineers in fields such as CNC systems, computer networks, digital electronics, etc. The conducted research, along with the implementation of dedicated VR environments for specific specializations, allows for the acquisition of valuable experience and knowledge in the development of this form of education—both within formal educational pathways and in supplementary learning. This work demonstrates the possibilities of adapting the didactic process to the evolving needs of industry through the use of VR.